ADP-Ribosylation Regulates the Signaling Function of IFN-γ - Menzel, Stephan; Koudelka, Tomas; Rissiek, Björn; Haag, Friedrich; Meyer-Schwesinger, Catherine; Tholey, Andreas; Koch-Nolte, Friedrich (Frontiers in Immunology, 2021)
Murine T cells express the GPI-anchored ADP-ribosyltransferase 2.2 (ARTC2.2) on the cell surface. In response to T cell activation or extracellular NAD+ or ATP-mediated gating of the P2X7 ion channel ARTC2.2 is shed from the cell surface as a soluble enzyme. Shedding alters the target specificity of ARTC2.2 from cell surface proteins to secreted proteins. Here we demonstrate that shed ARTC2.2 potently ADP-ribosylates IFN-γ in addition to other cytokines. Using mass spectrometry, we identify arginine 128 as the target site of ADP-ribosylation. This residue has been implicated to play a key role in binding of IFN-γ to the interferon receptor 1 (IFNR1). Indeed, binding of IFN-γ to IFNR1 blocks ADP-ribosylation of IFN-γ. Moreover, ADP-ribosylation of IFN-γ inhibits the capacity of IFN-γ to induce STAT1 phosphorylation in macrophages and upregulation of the proteasomal subunit ß5i and the proteasomal activator PA28-α in podocytes. Our results show that ADP-ribosylation inhibits the signaling functions of IFN-γ and point to a new regulatory mechanism for controlling signaling by IFN-γ.